TOTAL BACTERIA ON THE FECES LAYER IN VARIOUS AGE GROUPS - Baskara, Dewa Putu Pradipta; Besung, I Nengah Kerta; PG, Ketut Tono (Buletin Veteriner Udayana, 2021)
This study aims to determine the total number of bacteria isolated from laying hens at various ages. The sample used was healthy laying hens' feces with 24 samples using the pouring method. This study uses a completely randomized design (CRD). The data obtained were tested with the Least Significant Difference Test (LSD). The results showed the total number of bacteria in the starter phase of layer was 52.83x10 7 CFU/ml, grower phase of layer was 208.50x10 7 CFU/ml, developer phase of layer was 409.5x10 7 CFU/ml, and layer phases of layer was 208x10 7 CFU/ml. It can be concluded that the total number of bacteria in the layer is significantly different at each age phase.